Change in serum basic fibroblast growth factor level and its relationship to pulmonary arterial pressure in patients with acute exacerbation of chronic cor pulmonale on plateau - Yang, Sheng-yue (Zhongguo wei zhong bing ji jiu yi xue = Chinese critical care medicine = Zhongguo weizhongbing jijiuyixue, 2006)
OBJECTIVE: To assess the role of serum basic fibroblast growth factor (bFGF) in the development of hypoxic pulmonary hypertension in the patients with chronic cor pulmonale on highland (HACCP)